Experimental investigation on the physical parameters of ionic polymer metal composites sensors for humidity perception - Lijie Li (Sensors and Actuators B: Chemical, 2021)
Ionic polymer metal composite (IPMC) is one of typical electromechanical transducing materials integrating actuation and sensing functions. In this work, we systematically investigate the evolutions of the capacitance, surface resistance and ionic electrical response of strip shaped IPMC under different humidity conditions. For each parameter, we have performed a set of static and dynamic humidity sensing tests, considering the change of the thickness, cations type and impregnation-reduction plating (IRP) times. Through conducting a series of experiments, it is concluded that the humidity-capacitance sensing has achieved a much wider sensing range (22 % RH - 100 %RH in this work, comparing with 40 % RH - 90 %RH in previous work) and an increased sensitivity (256μF in this work, comparing with140nF in previous work). In the meantime, humidity-surface resistance sensing has the perception of the full humidity range. While the humidity-ionic electrical response sensing can only respond to dynamic humidity changes but showing a very fast response time less than 0.5 s, which will be of great significance in some special humidity detection scenarios, such as the rapid detection and alarm for leakage of equipment with constant humidity. For each case, it implies a fact that the water absorption capacity of surface electrode and inter layer determines the humidity sensing abilities, such as response speed, amplitude and so on.